Epistemological Questions for a Speculative Pragmatist - van Gemert, Ties (AM Journal of Art and Media Studies, 2021)
This essay will engage in a critical dialogue with Massumi’s concept of speculative pragmatism by reconstructing and interrogating the epistemology and metaphysics it presupposes. First, we will narrate and explicate the metaphysics embedded in the philosophy of speculative pragmatism. Secondly, we will recapitulate Massumi’s conceptualization of speculative pragmatism in his book Semblance and Event (2011). Our reading of this book will lead us to argue that speculative pragmatism can be reformulated as a philosophy of panperceptionism. The essay will end with some remarks and questions that aim to challenge the epistemology and metaphysics of speculative pragmatism. We will focus on Massumi’s synthesizing of the subject-object distinction, his theory of judgement, and his deflationary notion of truth. Article received: April 16, 2020; Article accepted: July 1, 2020; Published online: April 15, 2021; Original scholarly paper